Large-area flexible foamy copper-based boron-doped diamond film as well as preparation method and application thereof

By depositing TiO2 transition layer on the foam copper substrate and depositing a BDD film, the problem of poor expansion coefficient between the foam copper substrate and the BDD film is solved, and a flexible and flexible foam copper-based boron-doped diamond film is realized, which improves the electricity of the supercapacitor Chemical properties and cycle stability.

CN119194409APending Publication Date: 2024-12-27QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411317887.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, the difference in expansion coefficient between the foam copper substrate and the BDD film makes it difficult for the BDD film to deposit on the foam copper substrate, and the BDD film has a high rigidity and cannot be made into a flexible foldable electrode, which affects the discharge performance and cycle life of the electrode.

Method used

Using a large-area flexible foam copper-based boron-doped diamond film, the TiO2 transition layer is deposited on the foam copper substrate to improve the bonding force between copper and BDD film, and the flexibility of copper foam and the energy storage performance of BDD are used to prepare flexible Curved foamed copper-based boron-doped diamond film.

Benefits of technology

The flexible foldable function and charging and discharge function of the BDD film at room temperature are realized, the energy density and cyclic stability of the copper-based BDD supercapacitor are improved, and the preparation method of the flexible BDD-based supercapacitor is expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194409A_ABST
    Figure CN119194409A_ABST
Patent Text Reader

Abstract

The invention discloses a large-area flexible foamy copper-based boron-doped diamond film and a preparation method and application thereof.The large-area flexible foamy copper-based boron-doped diamond film comprises foamy copper, a transition layer and a BDD film, the foamy copper serves as a substrate, commercial large-area foamy copper is adopted as the foamy copper, a titanium dioxide atomic layer is adopted as the transition layer, the transition layer is deposited on the substrate, and the BDD film is arranged on the transition layer. The BDD film is deposited on the transition layer. The TiO2 atomic layer is deposited on the foamy copper substrate through the ALD technology to improve the film-substrate binding force of copper and the BDD film, the complete BDD film is obtained, the flexible folding function of the diamond film at the normal temperature can be achieved, and the charging and discharging functions at the normal temperature can also be achieved; the large-area flexible bendable foamy copper-based boron-doped diamond film is used for preparing the flexible capacitor, good electrochemical performance and high cycling stability are achieved, and the preparation method of the large-area BDD-based flexible supercapacitor is expanded to a great extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor materials, and in particular to a large-area flexible foam copper-based boron-doped diamond film and a preparation method and application thereof. Background Art

[0002] Boron-doped diamond, as a new type of carbon electrode material, has become a highly competitive supercapacitor electrode material due to its wide electrochemical window, high electrochemical stability, and strong acid-base corrosion resistance. The traditional two-dimensional closed electrode does not form a through-type interconnected pore structure, resulting in a small electrode surface area and low specific capacitance. Studies have shown that expanding the BDD (boron-doped diamond) design from two-dimensional to a three-dimensional porous structure can increase the electrode specific surface area and high mass transfer rate, thereby achieving the effect of increasing specific capacity. Among various porous substrates, foam materials have attracted a lot of attention due to their large specific surface area, light weight, and three-dimensional connectivity characteristics derived from high porosity. However, due to the difference in expansion coefficients between the commonly used substrate and the BDD film, the two parts of the structure expand asynchronously in volume under extreme conditions, causing the BDD film to peel off from the substrate, seriously affecting the electrode discharge performance and cycle life. Therefore, finding an economical and efficient method to solve the influence of the expansion coefficient between the foam substrate and the BDD film and prepare a porous foam BDD electrode with high energy density has become a difficulty in the current BDD-based energy storage field.

[0003] Commercial Ni foam and copper foam are typical non-carbide forming elements. In the chemical vapor deposition atmosphere, they will not form a carbide transition layer first like carbide forming elements, and then nucleate on the transition layer. Therefore, the adhesion of the BDD film is very poor. At present, in addition to the copper matrix alloying method, a transition layer with good bonding ability with both diamond and copper is introduced at the diamond / copper interface. The selection of the transition layer is very important. It must be able to bond with both copper and BDD. If the thickness of the carbide layer is too thin, the interface bonding is weak; if the thickness is too thick, additional interface stress will be generated. In recent years, the rise of atomic layer deposition technology has made it possible to deposit a complete BDD on a foam structure. It is because ALD can generate a film that is consistent with the original substrate shape, that is, the film can be uniformly deposited on a concave surface. However, there are few reports on the application of ALD technology to the preparation of porous BDD films, the realization of complete deposition of BDD films on the surface of copper foam, and the acquisition of high energy density copper-based BDD electrodes.

[0004] Therefore, how to use an ingenious method to obtain a complete and highly crystalline BDD film on a foam copper substrate has become a technical problem that needs to be urgently solved by technicians in this field. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art that the BDD film is difficult to deposit on the foam copper substrate due to the large difference in expansion coefficient between the foam copper substrate and the BDD film, and the BDD film is too rigid to be made into a flexible and foldable electrode. A large-area flexible foam copper-based boron-doped diamond film and a preparation method and application thereof are proposed. The flexible and bendable foam copper-based boron-doped diamond film is prepared by selecting the porosity of the foam copper, introducing a TiO2 transition layer to adjust the bonding strength between the copper substrate and the BDD film, and continuing to deposit the BDD film thereon. The flexibility of the foam copper substrate and the energy storage performance of the BDD film are utilized to prepare a flexible and bendable foam copper-based boron-doped diamond film with energy storage function, thereby providing a new solution for preparing a flexible BDD-based supercapacitor.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A large-area flexible foam copper-based boron-doped diamond film comprises: foam copper, a transition layer and a BDD film. The foam copper serves as a substrate, the foam copper adopts commercial large-area foam copper, the transition layer adopts a titanium dioxide atomic layer, the transition layer is deposited on the substrate, and the BDD film is deposited on the transition layer.

[0008] As a further technical solution of the present invention, the BDD film is a boron-doped diamond film.

[0009] The method for preparing a large-area flexible foam copper-based boron-doped diamond film comprises the following specific steps:

[0010] S1: Choose commercial copper foam as the substrate, rub the copper foam back and forth to increase its flexibility, then soak it in 0.1M hydrofluoric acid for 5 minutes, and finally place it in acetone and ethanol for 10 minutes each.

[0011] S2: Depositing a titanium dioxide transition layer with a thickness of one atomic layer on the substrate: heating titanium tetrachloride to evaporate, and cyclically depositing a titanium dioxide transition layer on the substrate for 200 growth cycles at a reaction chamber temperature of 210°C;

[0012] S3: depositing a BDD film on the titanium dioxide surface;

[0013] S31: Seeding: Soak the foam copper and titanium dioxide in diamond powder for 10 minutes and then take them out for use;

[0014] S32: Hot wire chemical vapor deposition coating: B2O3 is used as the boron source, ethanol is used as the growth and nucleation carbon source, and boron doping is achieved by hydrogen bubbling method.

[0015] As a further technical solution of the present invention, in S1, the porosity of the copper foam is 130 ppi, and the size of the copper foam is 15*15 cm 2.

[0016] As a further technical solution of the present invention, in S2, a corresponding completed growth cycle includes: the time for introducing titanium tetrachloride, nitrogen, water, and nitrogen is 0.15s, 30s, 0.15s, and 30s respectively.

[0017] The application of large-area flexible foam copper-based boron-doped diamond films includes applications in flexible capacitors. The preparation method of the flexible capacitor is as follows: a flexible capacitor device is assembled using two completely identical flexible foam copper-based boron-doped diamond films as positive and negative electrodes, respectively, and Na2SO4 / polyvinyl alcohol gel as the electrolyte.

[0018] As a further technical solution of the present invention, the flexible capacitor device has a current density of 0.4 mA·cm -2 When the power density is 0.16 mW·cm -2 and energy density of 2.31 mJ·cm -2 .

[0019] As a further technical solution of the present invention, at a current density of 1.0 mA·cm -2 Under the test results, the capacitance retention rate of the flexible capacitor device is 95% after 50,000 cycles of charge and discharge, and the capacitance retention rate is 95% after 100,000 cycles of charge and discharge.

[0020] The beneficial effects of the present invention are:

[0021] 1. The TiO2 atomic layer will be deposited on the foam copper substrate through ALD technology to improve the film-base bonding strength between copper and BDD film, and obtain a complete BDD film, which can realize the flexible and foldable function of diamond film at room temperature, and can also realize the charging and discharging function at room temperature.

[0022] 2. The area of ​​the commercial copper foam substrate is large enough, about 15*15cm 2 The prepared copper / Ti / BDD supercapacitor electrode is much larger than the currently reported BDD supercapacitor electrode.

[0023] 3. The equipment involved is HFCVD and ALD, both of which are mass-produced and have simple processes, and are therefore suitable for large-scale production of copper / Ti / BDD supercapacitor electrodes.

[0024] 4. Flexible capacitors are prepared using large-area flexible and bendable foam copper-based boron-doped diamond films, which have good electrochemical properties and high cycle stability, and have greatly expanded the preparation method of large-area BDD-based flexible supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1This is a schematic diagram of preparing a flexible and bendable copper-based boron-doped diamond film and electrode using foamed copper in Example 1 of the present invention;

[0026] Figure 2 Surface morphologies of BDD films with different pore densities in Example 1 of the present invention: fiber BDD films with a diameter of 0.2 mm (a, b, c, and d); fiber BDD films with a diameter of 0.3 mm (e, f, g, and h); fiber BDD films with a diameter of 0.4 mm (i, j, k, and l); fiber BDD films with a diameter of 0.5 mm (m, n, o, and p);

[0027] Figure 3 The BDD thin film electrodes with different diameters in Example 1 of the present invention are shown in Figure 1 at 100 mV·s -1 Electrochemical performance at scan rate;

[0028] Figure 4 The cyclic voltammetry curves of the fiber BDD film with a diameter of 0.4 mm in Example 1 of the present invention at different curvatures. DETAILED DESCRIPTION

[0029] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0030] A large-area flexible copper foam-based boron-doped diamond film comprises: copper foam, a transition layer and a BDD film. The copper foam is used as a substrate, the copper foam adopts commercial large-area copper foam, the transition layer adopts a titanium dioxide atomic layer, the transition layer is deposited on the substrate, and the BDD film is deposited on the transition layer.

[0031] The foam copper-based boron-doped diamond film can realize the flexible and foldable function of the diamond film at room temperature, and the foam copper-based boron-doped diamond film can also realize the charging and discharging function at room temperature.

[0032] In a preferred embodiment, the BDD film is a boron-doped diamond film.

[0033] The method for preparing a large-area flexible foam copper-based boron-doped diamond film comprises the following specific steps:

[0034] S1: Choose commercial copper foam as the substrate, rub the copper foam back and forth to increase its flexibility, then soak it in 0.1M hydrofluoric acid for 5 minutes, and finally place it in acetone and ethanol for 10 minutes each.

[0035] S2: Depositing a titanium dioxide transition layer with a thickness of one atomic layer on the substrate: heating titanium tetrachloride to evaporate, and cyclically depositing a titanium dioxide transition layer on the substrate for 200 growth cycles at a reaction chamber temperature of 210°C;

[0036] S3: depositing a BDD film on the titanium dioxide surface;

[0037] S31: Seeding: Soak the foam copper and titanium dioxide in diamond powder for 10 minutes and then take them out for use;

[0038] S32: Hot wire chemical vapor deposition coating: B2O3 is used as the boron source, ethanol is used as the growth and nucleation carbon source, and boron doping is achieved by hydrogen bubbling method.

[0039] In a preferred embodiment, in S1, the porosity of the copper foam is 130 ppi, and the size of the copper foam is 15*15 cm 2 , which is the largest area flexible and foldable BDD-based supercapacitor electrode reported so far.

[0040] In a preferred embodiment, in S2, a corresponding completed growth cycle includes: the time for introducing titanium tetrachloride, nitrogen, water, and nitrogen is 0.15s, 30s, 0.15s, and 30s, respectively.

[0041] The application of large-area flexible foam copper-based boron-doped diamond films includes applications in flexible capacitors. The preparation method of the flexible capacitor is as follows: a flexible capacitor device is assembled using two completely identical flexible foam copper-based boron-doped diamond films as positive and negative electrodes, respectively, and Na2SO4 / polyvinyl alcohol gel as the electrolyte.

[0042] The large-area flexible and bendable foam copper-based boron-doped diamond film obtained by the above simple and convenient preparation method can take into account the large area, flexible and foldable functions and excellent electrochemical properties. Therefore, it greatly expands the application of copper-based boron-doped diamond in the field of flexible supercapacitors.

[0043] In a preferred embodiment, the flexible capacitor device is -2 When the power density is 0.16 mW·cm -2 and energy density of 2.31 mJ·cm -2 .

[0044] In a preferred embodiment, at a current density of 1.0 mA·cm -2 Under the test results, the capacitance retention rate of the flexible capacitor device is 95% after 50,000 cycles of charge and discharge, and the capacitance retention rate is 95% after 100,000 cycles of charge and discharge.

[0045] Example 1

[0046] (1) The porosity of the selected copper foam is 110, 130, and 150 ppi, and the size is 15*15 cm 2Copper foam as substrate (such as Figure 1 a).

[0047] (2) Substrate pretreatment: First, rub the copper foam back and forth to increase its flexibility, then soak it in 0.1 M hydrofluoric acid for 5 min, and finally place it in acetone and ethanol for ultrasonic treatment for 10 min each.

[0048] (3) Titanium dioxide deposition: Titanium tetrachloride was heated to evaporate, and a titanium dioxide layer was cyclically deposited for 200 growth cycles at a reaction chamber temperature of 210°C. A corresponding completed growth cycle included: the time for introducing titanium tetrachloride, nitrogen, water, and nitrogen was 0.15 s, 30 s, 0.15 s, and 30 s, respectively.

[0049] (4) Hot wire chemical vapor deposition coating: The main deposition parameters of the film are: voltage 39V, current 104A, substrate temperature 700℃, gas pressure 3KPa, C / H ratio 1% and B / C ratio 400ppm; boron trioxide (B2O3) is used as the boron source, and boron doping is achieved by hydrogen bubbling method to prepare large-area flexible and bendable foam copper-based boron-doped diamond film.

[0050] The deposition process includes two steps: (a) the nucleation time is controlled to 0.2 h, during which ethanol is used as the carbon source for growing diamond films; the deposition parameters are: CH4:H2=10:1000 (sccm);

[0051] (b) The growth period was controlled to be 2 hours, during which ethanol was used as the carbon source for growing the BDD film; the deposition parameters were: H2 (bubble): B2O3 / H2 / C2H5OH: H2 = 25:50:1000 (sccm); Figure 1 As shown in c and d, the preparation is completed.

[0052] Scanning electron microscope image characterization: Figure 2 As shown, the crystallinity of the BDD films deposited on the surface of copper foam with different porosities is also different; it is obvious that the BDD film on the surface of copper foam with a porosity of 130ppi has better integrity and higher crystallinity, which is conducive to obtaining better electrochemical performance.

[0053] (5) Comparison of electrochemical performance: A three-electrode detection system was formed with Cu / Ti / BDD electrode as the working electrode, platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode. The detection results are shown in Figure 3 shown.

[0054] Depend on Figure 3 It can be seen that the Cu with a porosity of 130ppi 130 / Ti / BDD shows a larger area, indicating that it has the highest active specific capacity.

[0055] like Figure 4 As shown, the Cu 130 After the / Ti / BDD electrode was bent at different angles, its energy storage performance did not change much, which proved the bending flexibility of the Cu-based BDD thin film electrode.

[0056] (6) Preparation of capacitors: Two identical flexible Cu with a length of 1 cm and a width of 1 cm 130 The flexible capacitor device is assembled with / Ti / BDD electrodes as positive and negative electrodes, and Na2SO4 / polyvinyl alcohol gel as electrolyte. The performance test results are as follows: The flexible capacitor device has a current density of 0.4 mA cm -2 When the power density is 0.16 mW cm -2 and an energy density of 2.31 mJ cm -2 At the same time, at a current density of 1.0 mA cm -2 Under the test results, the capacitance retention rate of the flexible capacitor device is 95% after 50,000 cycles of charge and discharge, and the capacitance retention rate is 95% after 100,000 cycles of charge and discharge.

[0057] Example 2

[0058] The effect of the thickness of the TiO2 transition layer on the bending and folding function and energy storage performance of large-area flexible and bendable foam copper-based boron-doped diamond films was investigated.

[0059] (1) The porosity of the selected copper foam is 130ppi and the size is 15*15cm 2 Copper foam as the substrate.

[0060] (2) Substrate pretreatment: First, rub the copper foam back and forth to increase its flexibility, then soak it in 0.1 M hydrofluoric acid for 5 min, and finally place it in acetone and ethanol for ultrasonic treatment for 10 min each.

[0061] (3) Titanium dioxide deposition: Titanium tetrachloride was heated to evaporate, and a titanium dioxide layer was deposited cyclically for 100, 200, 300, and 400 growth cycles at a reaction chamber temperature of 210°C. A corresponding completed growth cycle included: the time for introducing titanium tetrachloride, nitrogen, water, and nitrogen was 0.3 s, 30 s, 0.3 s, and 30 s, respectively.

[0062] (4) Hot wire chemical vapor deposition coating: The main deposition parameters of the film are: voltage 39V, current 104A, substrate temperature 700℃, gas pressure 3KPa, C / H ratio 1% and B / C ratio 400ppm; boron trioxide (B2O3) is used as the boron source, and boron doping is achieved by hydrogen bubbling method to prepare large-area flexible and bendable foam copper-based boron-doped diamond film.

[0063] The deposition process includes two steps: (a) the nucleation time is controlled to 0.2 h, during which ethanol is used as the carbon source for growing diamond films; the deposition parameters are: CH4:H2=10:1000 (sccm);

[0064] (b) The growth period was controlled to be 2 hours, during which ethanol was used as the carbon source for growing the BDD film; the deposition parameters were: H2 (bubble): B2O3 / H2 / C2H5OH: H2 = 25:50:1000 (sccm); Figure 1 As shown in c and d, the preparation is completed.

[0065] Scanning electron microscope image characterization: The crystallinity of the BDD film deposited on the surface of the copper foam with different thickness of the titanium dioxide transition layer is also different; it is obvious that the BDD film on the surface of the copper foam with a porosity of 200 growth cycles and a transition layer thickness is better and has a higher crystallinity, which is conducive to obtaining better electrochemical properties.

[0066] (6) Comparison of electrochemical performance: A three-electrode detection system was formed with Cu / Ti / BDD electrode as the working electrode, platinum sheet as the counter electrode, and Ag / AgCl as the reference electrode. The detection results are shown in Figure 3 shown.

[0067] Depend on Figure 3 It can be seen that the transition layer thickness is 200 growth cycles of Cu 130 / Ti 200 / BDD shows a larger area, indicating that it has the highest specific capacity. 130 / Ti 200 / The energy storage performance of the BDD electrode does not change much when it is bent at different angles.

[0068] (6) Preparation of capacitors: Two identical flexible Cu with a length of 1 cm and a diameter of 1 cm 130 / Ti 200 / BDD electrodes are positive and negative electrodes respectively, and Na2SO4 / polyvinyl alcohol gel is used as the electrolyte (the assembled flexible capacitor device is tested and its performance results are as follows: Cu 130 / Ti 200 The symmetric supercapacitor composed of / BDD electrodes has a current density of 0.1 mA cm -2 When the power density is 3.2 mW cm -2 and an energy density of 13.5 mJ cm -2 .

[0069] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention (including the claims) is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0070] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. Large-area flexible foam copper-based boron-doped diamond film, characterized in that: include: Copper foam, transition layer and BDD film, the copper foam is used as a substrate, the copper foam adopts commercial large-area copper foam, the transition layer adopts a titanium dioxide atomic layer, the transition layer is deposited on the substrate, and the BDD film is deposited on the transition layer.

2. The large-area flexible foam copper-based boron-doped diamond film according to claim 1, characterized in that: The BDD film is a boron-doped diamond film.

3. The method for preparing a large-area flexible foam copper-based boron-doped diamond film according to claim 1, characterized in that: The specific steps include: S1: Choose commercial copper foam as the substrate, rub the copper foam back and forth to increase its flexibility, then soak it in 0.1M hydrofluoric acid for 5 minutes, and finally place it in acetone and ethanol for 10 minutes each. S2: Depositing a titanium dioxide transition layer with a thickness of one atomic layer on the substrate: heating titanium tetrachloride to evaporate, and cyclically depositing a titanium dioxide transition layer on the substrate for 200 growth cycles at a reaction chamber temperature of 210°C; S3: depositing a BDD film on the titanium dioxide surface; S31: Seeding: Soak the foam copper and titanium dioxide in diamond powder for 10 minutes and then take them out for use; S32: Hot wire chemical vapor deposition coating: B2O3 is used as the boron source, ethanol is used as the growth and nucleation carbon source, and boron doping is achieved by hydrogen bubbling method.

4. The method for preparing a large-area flexible foam copper-based boron-doped diamond film according to claim 3, characterized in that: In S1, the porosity of the copper foam is 130 ppi, and the size of the copper foam is 15*15 cm 2 .

5. The method for preparing a large-area flexible foam copper-based boron-doped diamond film according to claim 3, characterized in that: In S2, a corresponding completed growth cycle includes: the time for introducing titanium tetrachloride, nitrogen, water, and nitrogen is 0.15s, 30s, 0.15s, and 30s respectively.

6. The use of the large-area flexible foam copper-based boron-doped diamond film according to claim 1, characterized in that: Including applications in flexible capacitors, the preparation method of the flexible capacitor is: a flexible capacitor device is assembled using two completely identical flexible foam copper-based boron-doped diamond films as positive and negative electrodes, respectively, and Na2SO4 / polyvinyl alcohol gel as the electrolyte.

7. The use of the large-area flexible foam copper-based boron-doped diamond film according to claim 6, characterized in that: The flexible capacitor device has a current density of 0.4 mA cm -2 When the power density is 0.16 mW·cm -2 and energy density of 2.31 mJ·cm -2 .

8. The use of the large-area flexible foam copper-based boron-doped diamond film according to claim 7, characterized in that: At a current density of 1.0 mA cm -2 Under the test results, the capacitance retention rate of the flexible capacitor device is 95% after 50,000 cycles of charge and discharge, and the capacitance retention rate is 95% after 100,000 cycles of charge and discharge.